Role of Active Contraction and Tropomodulins in Regulating Actin Filament Length and Sarcomere Structure in Developing Zebrafish Skeletal Muscle - Mazelet, Lise; Parker, Matthew O.; Li, Mei; Arner, Anders; Ashworth, Rachel (Frontiers in Physiology, 2016)
Whilst it is recognized that contraction plays an important part in maintaining the structure and function of mature skeletal muscle, its role during development remains undefined. In this study the role of movement in skeletal muscle maturation was investigated in intact zebrafish embryos using a combination of genetic and pharmacological approaches. An immotile mutant line (cacnb1ts25) which lacks functional voltage-gated calcium channels (dihydropyridine receptors) in the muscle and pharmacological immobilization of embryos with a reversible anesthetic (Tricaine), allowed the study of paralysis (in mutants and anesthetized fish) and recovery of movement (reversal of anesthetic treatment). The effect of paralysis in early embryos (aged between 17 and 24 hours post-fertilization, hpf) on skeletal muscle structure at both myofibrillar and myofilament level was determined using both immunostaining with confocal microscopy and small angle X-ray diffraction. The consequences of paralysis and subsequent recovery on the localization of the actin capping proteins Tropomodulin 1 & 4 (Tmod) in fish aged from 17 hpf until 42 hpf was also assessed. The functional consequences of early paralysis were investigated by examining the mechanical properties of the larval muscle. The length-force relationship, active and passive tension, was measured in immotile, recovered and control skeletal muscle at 5 and 7 day post-fertilization (dpf). Recovery of muscle function was also assessed by examining swimming patterns in recovered and control fish. Inhibition of the initial embryonic movements (up to 24 hpf) resulted in an increase in myofibril length and a decrease in width followed by almost complete recovery in both moving and paralyzed fish by 42 hpf. In conclusion, myofibril organization is regulated by a dual mechanism involving movement-dependent and movement-independent processes. The initial contractile event itself drives the localization of Tmod1 to its sarcomeric position, capping the actin pointed ends and ultimately regulating actin length. This study demonstrates that both contraction and contractile-independent mechanisms are important for the regulation of myofibril organization, which in turn is necessary for establishing proper skeletal muscle structure and function during development in vivo in zebrafish.